(untitled) (La U Investiga, 2018)
Emphysematous cholecystitis is assumed to be a feared complication of acute cholecystitis due to the torpid, often fatal evolution that it usually causes. Its frequency, although low, is not totally defined, being the diagnosis of imaging choice, confirmed to the surgical act, which constitutes the fundamental basis of the treatment. Even so, regional and national scientific communications on their behavior have been minimal. We present a case of an elderly patient of 80 years, with presumptive sepsis of intraabdominal origin, secondary to acute emphysematous cholecystitis, confirmed to the surgical act and as a result of anatomopathological study. She continued hospitalization in the Intensive Care Unit, being diagnosed with right-sided Inflammatory Pneumopathy, an entity that prolongs her hospital stay and requires replacement of initial antibiotic therapy, in addition to serial determinations of paraclinical studies until hospital discharge is determined. The presentation presents the evolution of a patient with the diagnosis of emphysematous cholecystitis whose data could enrich the clinical stock of medical students and help to determine the behavior of it, at least in the country.